DOMED STRUCTURES IN UZBEK ARCHITECTURE: THE ARCHITECTURE OF MOSQUES, MAUSOLEUMS, AND MADRASAS - A. R. Abobakirov (Ecomind Press, 2025)
Domed architecture in Uzbekistan represents one of the most striking achievements of Islamic civilization in Central Asia, embodying a synthesis of structural ingenuity, spiritual symbolism, and aesthetic refinement that has defined the region’s monumental heritage for over a millennium. This paper examines the development, function, and meaning of domed structures in Uzbek architecture, focusing on mosques, mausoleums, and madrasas as the primary categories of religious and educational architecture. Drawing on architectural surveys, historical sources, and comparative stylistic analysis, the study investigates how domes were constructed, what symbolic significance they carried, and how their stylistic and technological features evolved across periods ranging from the Samanid dynasty through the Timurid Empire, the Khanates of Bukhara and Khiva, and into the modern era. Results demonstrate that the dome was not merely a structural solution for covering large spaces but also a symbol of heaven, eternity, and divine order, embodied in masterpieces such as the Samanid Mausoleum, the Gur-e Amir in Samarkand, the Kalon Mosque in Bukhara, and the Bibi Khanum Mosque. The study further reveals how madrasas such as those of Ulugh Beg in Samarkand and Khodja Akhror in Tashkent integrated domes into educational architecture, creating spaces of intellectual as well as spiritual transcendence. The discussion emphasizes both the continuity of traditional dome construction techniques and the creative adaptations that reflected cultural exchanges with Persian, Ottoman, and Indian traditions, while highlighting the unique regional identity of Uzbek domed architecture. The conclusion underlines the enduring significance of domed structures for Uzbek national identity and their global recognition as part of UNESCO’s World Heritage, affirming their role as living symbols of Central Asia’s cultural and architectural legacy.
Keywords: Uzbek Architecture; Domes; Mosques; Mausoleums; Madrasas; Islamic Architecture; Central Asian Heritage